From the high school classroom to the modern universitary laboratory. The evolution of the space for the teaching of Biology at the University of Murcia (1915-1936) - Marín Murcia, José Pedro (CIAN-Revista de Historia de las Universidades, 2023)
The insufficient space for the young University of Murcia, created in 1915, was completed with classrooms, cabinets and laboratories of the General and Technical High school of Murcia. As the institution grew in terms of students and subjects, the space became insufficient and the University moved to the building of the former School of El Carmen. It was there where José Loustau’s Chair of Mineralogy and Botany was provisionally installed, with two different spaces; on one part occupied by the classroom for theory classes and another which hosted the experimental laboratory. The process of moving to a building of its own with sufficient space culminated in 1934 during the Second Republic with a new building, in the centre of Murcia. In this paper we will focus on analysing the synergy established between secondary and higher education, as well as the social and political issues that would mark the future of the young university and the development of spaces for the teaching and research of modern biology in Murcia. Of particular importance will be the influence of the Central University of Madrid and its professors on Loustau, the university independence and the cultural and scientific extension programme in the University of Murcia during Loustau’s mandate.